Symbiont effector-guided mapping of proteins in plant networks to improve crop climate stress resilience - Rehneke, Laura; Schäfer, Patrick; Justus Liebig University Giessen (My University, 2024)
There is an urgent need for novel protection strategies to sustainably secure crop production under changing climates. Studying microbial effectors, defined as microbe-derived proteins that alter signalling inside plant cells, has advanced our understanding of plant immunity and microbial plant colonisation strategies. Our understanding of effectors in the establishment and beneficial outcome of plant symbioses is less well known. Combining functional and comparative interaction assays uncovered specific symbiont effector targets in highly interconnected plant signalling networks and revealed the potential of effectors in beneficially modulating plant traits. The diverse functionality of symbiont effectors differs from the paradigmatic immuno-suppressive function of pathogen effectors. These effectors provide solutions for improving crop resilience against climate stress by their evolution-driven specification in host protein targeting and modulation. Symbiont effectors represent stringent tools not only to identify genetic targets for crop breeding, but to serve as applicable agents in crop management strategies under changing environments.
Keywords: ddc:630